COMPARATIVE SURVIVABILITY OF PSEUDOMONAS FLUORESCENS RRB 11 IN DIFFERENT CARRIERS AND RHIZOSPHERE - P. P. JAMBHULKAR; PRATIBHA SHARMA (The Bioscan, 2012)
The bioformulation of Pseudomonas fluorescens RRb-11 was prepared using talc powder, kaolinite powder, barley bran, wheat bran and soybean bran as carrier substrate for the management of bacterial leaf blight of rice using seed treatment as delivery method. The survival of Pseudomonas fluorescens RRb-11 was tested from bioformulation at every 30 days of storage. The maximum survivability of P.fluorescens was observed in talc based bioformulation even up to 150 days after storage. On all substrate the population of RRb-11 decline evenly but population reduced drastically after 120 days of storage. No survival of RRb-11 was observed in bioformulation of wheat and soybean bran from 60 days of storage. The survivability of RRb-11 was also enumerated in rhizosphere where the talc based bioformulation caused slow reduction in population density of RRb-11 as compare with other bioformulations. However, the population density of RRb-11 in rhizosphere reduced more drastically soon after delivering it in the soil as compare with the bioformulation kept in storage.